A sequential development towards a unified approach to protein sequence comparison based on classified groups of amino acids - Ghosh, Soumen; Pal, Jayanta; Maji, Bansibadan; Bhattacharya, Dilip Kumar (International Journal of Engineering and Technology, 2018)
The methods of comparison of protein sequences based on different classified groups of amino acids add a significant contribution to the literature of protein sequence comparison. But the methods vary with choice of different classified groups. Therefore, the purpose of the paper is to develop a unified approach towards the analysis of protein sequence comparison based on classification of amino acids in different groups of different cardinality. The paper considers 4 group classification, 5 group classification and 6 group classifications of amino acids, and in each case it applies the unified method for comparing two types of protein sequences, viz., 9 proteins of ND5 category and 50 Corona virus Spike Proteins. The results agree with those, which were obtained earlier by other methods based on classified groups of amino acids. An-yway it is found that the present unified formula is relatively simpler and fundamentally different from the earlier ones. Further, it can be applied conveniently in comparison of protein sequences based on all different types of classified groups of amino acids.